[C12mim]Br: A Temperature‐dependent Phase Transfer Catalyst and Its Application for Aerobic Oxidative Synthesis of 2‐Aryl Benzimidazoles, Benzoxazoles or Benzothiozoles Catalyzed by TEMPO Based Ionic Liquid. Issue 5 (17th February 2014) - Yu, Jiatao; Lu, Ming
Abstract The application of [C12mim]Br ionic liquid/o‐xylene temperature‐dependent biphasic system into the [Imim‐TEMPO][Cl]/O2‐promoted condensation between o‐phenylenediamines, o‐aminophenol or o‐aminothiophenol with aldehydes for preparing benzimidazoles, benzoxazoles or benzothiozoles is described. Several aldehydes and o‐phenylenediamines, o‐aminophenol or o‐aminothiophenol were reacted efficiently to form corresponding products in excellent yields. Both the [Imim‐TEMPO][Cl] and [C12mim]Br could be reused at least eight times without significantly decreasing the catalytic activity.